2020
DOI: 10.1039/d0ee00788a
|View full text |Cite
|
Sign up to set email alerts
|

Preventing phase segregation in mixed-halide perovskites: a perspective

Abstract: Halide segregation represents a severe stability problem for certain mixed-halide perovskites. Here we explore a myriad of methods for mitigating halide segregation, including several largely unexplored approaches that show significant promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
310
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(335 citation statements)
references
References 158 publications
7
310
0
1
Order By: Relevance
“…Defect-mediated halide segregation upon photoexcitation or current injection has also been widely used. [139][140][141][142] This model suggests that the halide segregation is a result of electric field-induced ionic movement. When the excited charge carriers, created by the photo-absorption or current injection, are caught by the trap states, an electric field pointing toward the surface of the film can be formed.…”
Section: Current Understandingsmentioning
confidence: 98%
See 2 more Smart Citations
“…Defect-mediated halide segregation upon photoexcitation or current injection has also been widely used. [139][140][141][142] This model suggests that the halide segregation is a result of electric field-induced ionic movement. When the excited charge carriers, created by the photo-absorption or current injection, are caught by the trap states, an electric field pointing toward the surface of the film can be formed.…”
Section: Current Understandingsmentioning
confidence: 98%
“…[126] A considerable amount of studies have reproduced the effects since the first report, yet with mixed success. [127] Studies by MaMeekin et al show that the spectral stability of mixed halide perovskites is closely relevant to the composition. [128] As illustrated in Figure 4.5, under identical illumination conditions, FA0.83Cs0.17Pb(I0.6Br0.4)3 perovskite exhibits better color stability in contrast to MAPb(I0.6Br0.4)3.…”
Section: Early Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,22,28 The extend and kinetics of this process have been reported to be dependent on the excitation density, 29 excitation energy, 30 laser repetition rate, 31 surrounding atmosphere, 31 temperature, 17,32 grain size, [33][34][35] and composition. 26,27 Under sufficiently low excitation densities halide segregation is not observed, indicating a certain threshold needed to trigger the segregation. 20,32,37,38 Moreover, an enhanced segregation is observed with increasing excitation density 29,31 but also stabilization effects showing a higher final Br content have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3 Device performance of mixed halide perovskites is however hampered by compositional instabilities under illumination in which segregated phases of low and high bromide content form. 17,18 Since the first report by Hoke et al 17 this phenomenon has been widely studied 17,[19][20][21][22][23][24][25] and recent reviews can be found by Knight et al 26 and Brennan et al 27 Several mechanisms driving halide segregation were hypothesized including pathways to mitigate it, but no holistic picture of the process has evolved so far.…”
Section: Introductionmentioning
confidence: 99%